LEGAL PERSPECTIVE IN CREATING EMPLOYMENT POLICIES FOR MINIMUM WAGE PAYMENT SYSTEMS IN THE COMPANY - Endeh Suhartini (Saburai International Journal of Social Sciences and Development, 2017)
Wages or salaries is an income, but the income does not always in term of Wages or salaries. Revenue that is also the type of other income, for example, profits from the sales of goods entrusted to someone, as brokerage commissions and other income in the administration in the form fees.The policies of payment of wages have been the problems that always lead to conflict which was never completed from year to year.Determination of remuneration policies, especially for employers and workers are expected to provide fairness and legal certainty in the implementation of the employment relationship so that the interests of the parties according to expectations in providing the realization of rights and obligations, as appropriate.Policies include wage-setting authority to wage determination process, the implementation of the wage, calculation, and payment of wages and wage control that must be done continuously by the Government.